International business particularly that centered on foreign direct investment - العامري محمد علي ابراهيم; نعمة نغم حسين (Journal of Economics and Administrative Sciences, 2007)
: While practicing of International business particularly that centered on foreign direct investment, let on one side, to achieving objectives of transnational corporations specially that represented in continuous pursue to improving its cash flows and maximization of stockholders wealth which is considered the most important objective to the transnational corporations, but in the same time its lead, on other side, to increasing the foreign exchange risk exposuring these corporations. So, the transnational corporations (TNCs) struggling to make strategies which are dealing in smart way, with this risk and its management in way that enable to avoiding risk completely or minimizing it, because this issue has a big important in international financial studies , and take a big part from the work of financial manager and his decisions.